Learning and teaching: the extent to which school principals in Irish voluntary secondary schools enable collaborative practice. Issue 4 (2nd October 2022) - Moynihan, Joseph Anthony; O'Donovan, Margaret
Abstract : Policy-makers in Ireland advocate teacher collaboration as being a vital component of educational reform and school improvement in inclusive and participatory communities of practice. The objective of this research study was to attempt to achieve a depth of understanding of the role played by principals in the reification of the Department of Education and Skills (DES) policy around collaborative practice in their schools. This paper attempts to capture a snapshot of the current culture around teacher collaborative practice and the extent to which such practice is enabled and/or encouraged by senior management. A qualitative approach was used to gather the necessary data which were analysed using a grounded theory approach. Some key findings include: principals have an astute awareness of how collaborative practice is conceptualised and contextualised within the Irish education system; there exists a broad range of formal and informal practices already at play; principals believe that clear structures and strategies will herald the creation of a new pedagogical landscape propagated by meaningful and highly effective collaborative practice; school leaders actively encourage and endorse collaborative practice; principals are positively seeking to re-culture schools and mediate the traditional norms that many teachers are essentially fearful to forsake.